Factors that predict taking restaurant leftovers: Strategies for reducing food waste. Issue 1 (26th December 2017) - Hamerman, Eric J.; Rudell, Fredrica; Martins, Chrissy M.
Abstract: Food waste is an important topic of environmental and societal concern. One method of reducing food waste is for patrons to take their restaurant leftovers home for future consumption. The current research applies impression management to determine the factors behind consumers' willingness to do so. Study 1 manipulated social situation (the identity of one's dining companions) and initiating behavior (whether the server established taking leftovers as a normative behavior based on proactively offering to wrap them). When people envisioned dining with others who they wanted to impress, perceived likelihood of taking home leftovers was greater when the server proactively offered to wrap the leftovers (vs. when the customer had to initiate the request). This difference did not hold true when considering dining companions with whom they were comfortable. Greater concern for the environment also increased willingness to take home leftovers. A second study investigated the process behind this result. Participants rated the social desirability of taking restaurant leftovers in various scenarios related to social situation and initiating behavior. Among dining companions who people wanted to impress, taking home leftovers was considered more embarrassing and a greater violation of social norms when the customer (vs. the server) initiated the discussion of taking leftovers. This difference did not occur for dining companions with whom they were comfortable. Concern for the environment did not affect this perception. The server offering to wrap leftovers was perceived as a positive indicator for customer service. Implications for consumer behavior, marketing strategy, and public policy are discussed.